PENGARUH KOMPETENSI DAN MUTASI TERHADAP KINERJA KARYAWAN - Sartika Yuliana (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2020)
Abstract : Competence is an important issue in a company because if a company has an employee who does not have this competence will harm the company in its development, because it is the competence is a basic characteristic of a person which enables it provide superior performance in a job, role or situation. Likewise, the mutation is also an important thing to be noticed by the leadership of a company because one of the employees will mutate a hedge against performance. In this study of two independent variables studied cypress only variables that significantly influence the performance of employee at PT. Pos Indonesia Solok competence. While variable mutation has no significant effect on the performance of employees of PT. Pos Indonesia Solok. Population and sample in this study amounted to 52 people. Keywords: Competence, Mutation and Performance